Методи управління надійністю надання послуг в мультисервісних мережах - Копитова, О. О. (My University, 2012)
В запропонованій дисертації отримав подальший розвиток метод оптимізації розподілу трафіку в мультисервісній мережі на основі веб-орієнтованої архітектури за рахунок використання додаткових елементів, що забезпечують маршрутизацію запитів при доступі до послуг. Пропонується використання методу ймовірнісно-часових графів та утворюючих функцій. Запропоновано метод реалізації процедури вибору екземпляру сервісу, який дозволяє забезпечити максимальну ефективність роботи системи мережного управління. В рамках даного методу розроблено підхід до локалізації несправностей в мультисервісних мережах на основі веб-орієнтованої архітектури. Це дозволяє підвищити якість обслуговування за рахунок своєчасного виявлення проблем, зменшення часу їх усунення, скорочення простоїв, і, як наслідок, покращення показників надійності надання послуг. Отримані в дисертації результати знайшли практичне застосування при виконанні науково-досвідної роботи, при розробці системи балансування трафіку в мультисервісній мережі ТОВ "Геймлофт" та в учбовому процесі. Dissertational work is devoted to the actual scientific problem related to the improving the quality of service in multiservice networks by improving management practices in services, namely the implementation of monitoring procedures the status and troubleshooting. Has been further developed an optimization method for distribution of traffic in multiservice networks based on Web-oriented architecture through the use of additional elements that provide the routing of user requests for access to the service. The mathematical apparatus of evaluating the effectiveness of the proposed method used the method of probability-time graphs and generating functions. Improved an implementation method of procedures for selecting copies of a service that allows to maximize the efficiency of network management systems of multiservice networks. Investigations of the effectiveness of management processes fault recovery. According to the research proposed a classification of types of faults in multi-service networks. Based on the proposed classification was improved fault management method. Under this method, an approach to fault isolation in multi-service networks based on Weboriented architecture. The proposed method allows to control and fault management in multiservice networks in order to determine their causes, thus enhancing the quality of service through timely detection of problems, reducing the time to address them, and, consequently, promotes the values of reliability of services.
Keywords: система мережного управління; мультисервісна мережа; веб-орієнтована архітектура; ймовірнісно-часовий граф; екземпляр сервісу; reliability; network management; multi-service network; Web-oriented architecture; the probabilistic-time graph; a copy of the service